The demographic determinants of development in the Lower Silesia region by the year 2050 - Rynio, Dorota (Uwarunkowania demograficzne rozwoju Dolnego Śląska do 2050 roku, 2020)
The provision of the conditions for continued socio-economic development is one of the fundamental objectives for regions. In an age of intensive changes in the global economy, demographic determinants seem to play a heightened role, as the quality and supply of human resources in regions largely determine their capabilities and paths of development. This paper aims to provide a forecast of the long-term demographic changes expected to arise in the Lower Silesia region of Poland, along with their projected effects upon the development potential of the region as a whole. This study was prepared on the basis of publicly available statistical and prognostic data for the period between 2010 and 2050. For research purposes, the region of Lower Silesia was assumed to correspond with the administrative area of the Lower Silesia voivodeship. The study employs the following research methods: literature studies, simple statistical methods, and ratiocination from statistical data
Biblioteka Regionalisty, 2020, Nr 20, s. 137-152
Keywords: development; region; Lower Silesia; economic analysis of population; rozwój; województwo dolnośląskie; analiza ekonomiczna wieku ludności